(untitled) (Theatrum historiae, 2020)
Following article reflects the social role, image and responsibilities of the midwives in Bohemia in the mid nineteenth up to the mid twentieth century, the period during which the position and image of the midwives significantly changed. In terms of time period the article analyses the time span when the professionalization of medicine is evolving to that extent that it begun also affect midwives: on the one hand, they remain personally connected with the female community and stand on the margin of the emerging obstetric science, on the other hand they became increasingly subject to official disciplinary authorities and regular inspections.